A comparison of bird foraging preferences for fruits of indigenous and alien shrubs and seed dispersal potentials in the Cape Floristic Region - Mokotjomela, Thabiso Michael (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.